2023
DOI: 10.1039/d3qo00066d
|View full text |Cite
|
Sign up to set email alerts
|

Highly regioselective C–H carbonylation of alkenes with phenyl formateviaaryl to vinyl 1,4-palladium migration

Abstract: We report herein a palladium-catalyzed C–H carbonylation of gem-disubstituted ethylenes with phenyl formate as a convenient CO surrogate through an aryl to vinyl 1,4-palladium migration, providing a wide range of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…The formation of methyl ortho ‐ tert ‐butyl‐ trans ‐cinnamate 4 clearly suggested that the palladium species migrate from neophentyl carbon center to ortho ‐position of the phenyl ring (from 5 to 6 ). Later, this “through space” palladium/hydrogen migration process has been proved to be quite general by studies from the research groups of Larock, [4b–c] Zhu, [4e] Baudoin, [4f–i] Feng [4j–o] and et al [4n–r] . Mechanistically, the migration was proposed to take place through the formation of a five‐membered palladacycle, which could further undergo reductive elimination or protonation to generate the rearranged palladium species (Scheme 1b).…”
Section: Introductionmentioning
confidence: 98%
“…The formation of methyl ortho ‐ tert ‐butyl‐ trans ‐cinnamate 4 clearly suggested that the palladium species migrate from neophentyl carbon center to ortho ‐position of the phenyl ring (from 5 to 6 ). Later, this “through space” palladium/hydrogen migration process has been proved to be quite general by studies from the research groups of Larock, [4b–c] Zhu, [4e] Baudoin, [4f–i] Feng [4j–o] and et al [4n–r] . Mechanistically, the migration was proposed to take place through the formation of a five‐membered palladacycle, which could further undergo reductive elimination or protonation to generate the rearranged palladium species (Scheme 1b).…”
Section: Introductionmentioning
confidence: 98%